Experimental Study on Electric Resistivity Characteristics of Compacted Loess under Different Loads and Drying-Wetting Cycles - Yu Zhou; Guoyu Li; Wei Ma; Dun Chen; Fei Wang; Yuncheng Mao; Qingsong Du; Jun Zhang; Liyun Tang (Advances in Civil Engineering)
Densely compacted loess foundations of many man-made infrastructures are often exposed to various loads and extreme weathering processes (e.g., drying-wetting cycles), which significantly deteriorate their mechanical properties. Traditional methods applied to characterize soil engineering properties are primarily based on visual inspections, point sensors, or destructive approaches, the results of which often have relatively high costs and cannot provide large-area coverage. The electrical resistivity method is a reasonable alternative that provides a nondestructive, sensitive, and continuous evaluation of the soil physical properties. Thus, the relationships between electrical resistivity and soil strength should be understood, particularly for scenarios in which soils undergo significant loads and cycles of drying and wetting. In this study, a suite of laboratory tests simulating loads (consolidation tests, unconfined compression tests, and uniaxial cyclic unloading-reloading tests) and seasonal field conditions (drying-wetting cycle tests) were conducted to quantitatively assess their deterioration effects on the geophysical and geotechnical properties of compacted loess. The experimental results indicated that electric resistivity decreases with the increase in stress and then approaches a stable value after the stress becomes 200 kPa. During the uniaxial compression process, the electric resistivity corresponds to both the stress and strain of loess in real-time. The electrical resistivity of loess reflects plastic damage under uniaxial unloading-reloading tests, but it is deficient in representing the dissipated energy of loess. The electrical resistivity of loess samples increases as the number of drying-wetting cycles increases but decreases with increasing cycle numbers after stabilization under consolidation load. The electrical resistivity can effectively characterize the mechanical and deformation characteristics of loess samples under loads and drying-wetting cycles, exhibiting a certain potential for long-term monitoring of soil engineering properties.